Assessment of EMI chokes under realistic loading conditions - Deng, Junhong (2010)
A novel measurement method has been developed to characterize the common-mode (CM) and differential-mode (DM) impedances of power line EMI chokes under realistic loading conditions. With a proper pre-measurement calibration process, all parasitic effects in the measurement setup can be eliminated. The measurement allows designer to assess the EMI suppression performance of these chokes with reasonable accuracy under various loading conditions. With the measurement results, a proper choke with optimum EMI suppression performance could be selected for a specific loading condition.